The deadline effect : how to work like it's the last minute--before the last minute - Cox, Christopher, (Journalist) (Avid Reader Press, 2021)
"Perfectionists and procrastinators alike agree--it's natural to dread a deadline. Whether your goal is to complete a masterpiece or just check off an overwhelming to-do list, the ticking clock signals despair. Christopher Cox knows the panic of the looming deadline all too well--as a magazine editor, he has spent years overseeing writers and journalists who couldn't meet a deadline to save their lives. After putting in a few too many late nights in the newsroom, he became determined to learn the secret of managing deadlines. He set off to observe nine different organizations as they approached a high-pressure deadline. Along the way, Cox made an ever greater discovery: these experts didn't just meet their big deadlines--they became more focused, productive, and creative in the process"--